2014
DOI: 10.1017/s0954579414000571
|View full text |Cite
|
Sign up to set email alerts
|

Associations between trajectories of perceived racial discrimination and psychological symptoms among African American adolescents

Abstract: Many African American adolescents experience racial discrimination, with adverse consequences; however, stability and change in these experiences over time have not been examined. We examined longitudinal patterns of perceived racial discrimination assessed in grades 7 – 10 and how these discrimination trajectories related to patterns of change in depressive and anxious symptoms and aggressive behaviors assessed over the same 4-year period. Growth mixture modeling performed on a community epidemiologically-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
79
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 100 publications
(189 reference statements)
7
79
1
1
Order By: Relevance
“…To date, the evidence for the presence and direction of racial/ethnic disparities in depressive symptoms during adolescence, particularly black-white differences, has been mixed, as has evidence for the relationships of SES markers to depression in adolescence and young adulthood. Higher levels of discrimination have been found among individuals with disadvantaged social status, 21 including racial and ethnic minorities, 21,25,26,29,30,39 and have also been shown to have an inverse relationship with mental health. 22 However, to our knowledge, no prior study has documented the high levels of discrimination among black young adults from highly educated families that we demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the evidence for the presence and direction of racial/ethnic disparities in depressive symptoms during adolescence, particularly black-white differences, has been mixed, as has evidence for the relationships of SES markers to depression in adolescence and young adulthood. Higher levels of discrimination have been found among individuals with disadvantaged social status, 21 including racial and ethnic minorities, 21,25,26,29,30,39 and have also been shown to have an inverse relationship with mental health. 22 However, to our knowledge, no prior study has documented the high levels of discrimination among black young adults from highly educated families that we demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,2527 In turn, perceived racial discrimination correlates with low psychological well-being among racial and ethnic minority youth. 19,2830 Whether perceived discrimination accounts for some or all of the influence of low SES on depression in adolescence is unknown, as is whether the influence of discrimination is the same across racial/ethnic groups. Although Brody et al showed that high SES non-Hispanic black 5 th graders had lower levels of perceived racial discrimination but reported greater increases in discrimination across early adolescence than their lower SES non-Hisapnic black peers, 19 to our knowledge, no study has explored if and how perceived discrimination in childhood and adolescence affects the relationships between SES, race, and depression during the transition into adulthood.…”
mentioning
confidence: 99%
“…A review of recent cross-sectional and longitudinal studies involving adolescents shows a considerable amount of heterogeneity in exposure to interpersonal discrimination (Brody, Lei, Chae, Yu, Kogan, & Beach, 2014; Richardson, Macon, Mustafaa, Bogan, Cole-Lewis, & Chavous, 2015; Smith, Reynolds, Fincham, & Beach, 2015; Smith-Bynum, Lambert, English, & Ialongo, 2014). These studies show that African American adolescents’ encounters with interpersonal discrimination are best characterized by qualitatively different subgroups, with many youth encountering low and increasing exposures to racial discrimination and others encountering more frequent experiences with racial discrimination.…”
mentioning
confidence: 99%
“…In this study, we concentrated on this type of bullying, because Spain is one of the main host countries for immigrants (Pajares, 2009). In this context, many immigrant students in Spain are bullied because of racial discrimination (Ávila, 2013) with disastrous consequences for their development, such as anxiety, or development of aggressive behavior (Smith et al, 2014). …”
Section: Introductionmentioning
confidence: 99%